IMPROVING STUDENTS’ WRITING SKILL IN IMAGINATIVE RECOUNT TEXT BY USING ROMANCE MOVIE AT ELEVENTH GRADERS OF TAKHASUSS AL-QUR’AN SENIOR HIGH SCHOOL - Aulia Isnaini Annisa; Buntara Adi Purwanto (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
The senior high school students faced some writing difficulties. The students are having a lot of difficulties with their English because writing requires procedure and organization, it deals with a variety of concepts, vocabulary, and grammar. Based on the problems above, the researcher focuss on the students’ problem and how to improve students’ writing skill by using romance movie. The researcher used experimental research. The research had conducted with treatment, which each all consists of four meetings. The location of the research was done at SMA Takhasuss Al-Qur’an with 40 students. The sample of this research wereXI bahasa 2 program as experiment group and XI bahasa 1 program as control group. The findings indicated that the application of romance movie were significant to improve the students’ writing in imaginative recount text. It was proved by that there was significant difference between the mean score of experimental class post test was 85,5 which was higher than the control class that only 69,5.